Effect of microwave treatment on longitudinal air permeability and preservative uptake characteristics of chir pine wood - Kumar Poonia, Pawan; Kumar Hom, Sanjeet; Sihag, Kapil; Tripathi, Sadhna (Maderas. Ciencia y Tecnología, 2016)
Low permeability of many wood species due to their anatomical properties causes problems during timber drying as well as impregnating with preservatives and resins. Microwave (MW) treatment influences heartwood permeability and improves preservative uptake and distribution. In the present study, microwave treatment of chir pine (Pinus roxburghii) wood was done at 2,45 GHz frequency at different level of intensity and radiation time. The gas permeability of chir pine wood was measured in an in-house built apparatus. Preservative uptake was tested using acid copper chromate (ACC) preservative by a dipping process. The effect of radiation intensity and time on preservative uptake and air permeability were studied. The results revealed remarkable increase in longitudinal wood air permeability and preservative uptake with the increase of intensity and time of treatment. The results indicate that this technology can be tested and applied on pilot scale for application in wood preservation industry.